Optimalisasi AI sebagai Asisten Pembelajaran: Integrasi Teknologi dengan Etiket Digital Bagi Guru di Sekolah Dasar [Optimizing AI as a Learning Assistant: Integrating Technology with Digital Etiquette for Teachers in Elementary Schools] - akhwani, akhwani; Rulyansah, Afib; Rahayu, Dewi Widiana; Rihlah, Jauharotur (Indonesia Berdaya, 2026)
Abstract. This community service activity is motivated by the rapid advancement of AI in education and the need for teachers to adapt to changing times. Many teachers are still unprepared and less responsive in utilizing AI optimally. Teachers’ understanding and digital skills need to be balanced with digital etiquette. The use of AI is not only about technical proficiency but also ethical considerations. Training on optimizing AI as a learning assistant should be accompanied by digital etiquette intervention. The aim of this community service is to improve teachers’ understanding and skills in using AI, as well as to integrate digital etiquette into teaching practices. The community service method used is the drill and practice model with the ORPAER cycle (observe, reflect, plan, action, evaluation, reflect). The results show an increase in the integration of AI in terms of teachers’ understanding and skills in learning activities. Additionally, teachers’ awareness of digital etiquette when utilizing AI has also improved. Teachers’ digital etiquette needs to be nurtured and developed. This community service succeeded in enhancing teachers’ proficiency both technically and ethically. Teachers need to participate in similar training and continuously improve their understanding, including practical ethics. As role models for digital etiquette, teachers must possess responsibility and morality in utilizing AI. Ethics apply not only in the virtual world but also in the real world. Abstrak. Pengabdian kepada Masyarakat ini dilatarbelakangi oleh pesatnya kemajuan AI di bidang pendidikan dan kebutuhan guru untuk adaptif terhadap perkembangan zaman. Banyak guru yang masih belum siap dan sigap memanfaatkan AI secara optimal. Pemahamana, keterampilan digital guru perlu diimbangi dengan etiket digital. Pemanfaatan AI tidak sekedar kecakapan teknis tetapi juga etis. Pelatihan optimaliasi AI sebagai asisten pembelajaran perlu diintervensi dengan etiket digital. Tujuan dari pengabdian kepada masyarakat ini adalah untuk meningkatkan pemahaman, keterampilan guru dalam menggunakan AI serta mengintegrasikan etiket digital dalam praktik pembelajaran. Metode pengabdian kepada masyarakat yang digunakna adalah model drill and practices dengan menggukan siklus ORPAER (observe, reflect, plan, action, evaluation, reflect). Hasil pengabdian menunjukkan terdapat peningkatan pada integrasi AI pada aspek pemahaman dan keterampilan AI dalam pembelajaran. Selain itu kesadaran guru terhadap etiket digital dalam memanfaatkan AI juga meningkat. Etiket digital guru perlu ditumbuhkembangkan. Pengabdian kepada Masyarakat berhasil meningkatkan kecakapan guru dari segi teknis dan etis. Guru perlu mengikuti pelatihan sejenis dan meningkatkan pemahamannya secara berkelanjutan, termasuk etika praktis. Guru berperan sebagai teladan etiket digital maka guru harus memiliki tanggung jawab dan moral dalam memanfaatkan AI. Etika tidak hanya di dunia maya tetapi juga di dunia nyata.